THE EFFECT OF TAX SANCTIONS ON INDIVIDUAL TAXPAYER COMPLIANCE AT KPP PRATAMA JAKARTA PASAR REBO - Hoiriah Hoiriah; Denny Erica (Sean Institute, 2023)
Taxes are Indonesia's largest source of income as reflected in the State Revenue and Expenditure Budget. In addition, taxes are also one of the sources of APBN revenues that the government can use to finance national development. In order to increase sources of government tax revenue, the government issued several regulations and laws related to tax sanctions in the hope of influencing the level of taxpayer compliance. This study examines whether tax sanctions affect individual taxpayer compliance in Indonesia and the results of the hypothesis test calculations are t test and f test using SPSS version 23 with a value of t (16.009) > t table (1.677) and f -score (256.297) > f-table (4.04), then the form of tax consequences has a significant effect on taxpayer compliance.